2005
DOI: 10.1375/twin.8.4.392
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Prevalence of DSM-IV and Latent Class-Defined ADHD Subtypes in a Population-Based Sample of Child and Adolescent Twins

Abstract: The goal of this study is to determine the prevalence and age of onset of Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSMIV; American Psychiatric Association, 1994) and latent class-derived attention deficit/hyperactivity disorder (ADHD) subtypes in a population-based twin sample of boys and girls. Missouri birth records identified families with a twin pair 7 to 18 years of age. Telephone screening interviews for ADHD symptoms were completed for 5007 families. Diagnostic assessments were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 38 publications
1
30
1
Order By: Relevance
“…No comparable studies have been conducted in a non-twin sample. As noted in Neuman et al, 2005, the prevalence of ADHD subtypes in Australian non-twin siblings of twins is similar to that reported in Missouri twins . Whether there would be differences in comorbidity profiles for non-twins is unknown.…”
Section: Limitationssupporting
confidence: 80%
“…No comparable studies have been conducted in a non-twin sample. As noted in Neuman et al, 2005, the prevalence of ADHD subtypes in Australian non-twin siblings of twins is similar to that reported in Missouri twins . Whether there would be differences in comorbidity profiles for non-twins is unknown.…”
Section: Limitationssupporting
confidence: 80%
“…This proportion was significantly higher (p<.0001) than that found in the general population: 3-9% (Airaksinen, Michelsson, & Jokela, 2004;Neuman et al, 2005). Nine boys (52.94%) and six girls (46.15%) in our dataset had a co-morbid diagnosis of ADHD.…”
Section: Co-morbiditycontrasting
confidence: 55%
“…Many clinical conditions characterised by impaired impulse control are more prevalent in males than females. For example, a survey with over 9000 respondents revealed that men have a higher risk of impulse control and substance use psychiatric disorders (Kessler et al, 2005) while Attention Deficit and Hyperactivity Disorder (Neuman et al, 2005) and conduct disorder (Eme and Kavanaugh, 1995) are also more prevalent in males. Whether or not such disorders, which are multi-faceted and may have multiple causes, reflect inherent differences in how males and females implement inhibitory control is unknown.…”
Section: Introductionmentioning
confidence: 99%